2005
DOI: 10.1152/ajpheart.00189.2004
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor mediates late cardiac dysfunction after burn injury

Abstract: . Macrophage migration inhibitory factor mediates late cardiac dysfunction after burn injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…However, MIF is also expressed in several tissues, including the heart, in which it has a physiologic role during ischemia (29). The current results indicate that endogenous cardiac MIF inhibits activation of the JNK pathway and limits myocardial reperfusion injury after ischemia.…”
Section: Discussionmentioning
confidence: 53%
“…However, MIF is also expressed in several tissues, including the heart, in which it has a physiologic role during ischemia (29). The current results indicate that endogenous cardiac MIF inhibits activation of the JNK pathway and limits myocardial reperfusion injury after ischemia.…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies have shown that MIF is expressed in the myocardium (11,16) and that MIF neutralization by anti-MIF antibody reversed endotoxin or burn injury-induced cardiac dysfunction (11,50). Anti-MIF treatment also protected TNF-␣ knockout mice, which were sensitive to CLP and succumbed quickly to uncontrolled infection from lethal peritonitis induced by CLP (11).…”
Section: Discussionmentioning
confidence: 99%
“…79 Similarly, MIF has been shown to mediate the late and prolonged cardiac depression after burn injury associated with major tissue damage that was restored by anti-MIF treatment. 80 Notably, an increase in MIF within the alveolar space during late experimental sepsis or MIF instilled exogenously into the lungs induced kinase activation and phosphorylation in the heart, eg, of MAPK, as indicative of myocardial depression, suggesting that MIF released from the lungs during sepsis may in part be responsible for the cardiac dysfunction accompanying sepsis. 81 A crucial role of MIF also has been revealed in the pathogenesis of experimental autoimmune myocarditis, as shown by antibody neutralization, which inhibited the onset and reduced the severity of disease in a therapeutic setting.…”
Section: Mif Contributes To Myocardial Dysfunction and Sepsismentioning
confidence: 99%